2017
DOI: 10.1021/acs.chemmater.6b04848
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Composition Tunable Formamidinium Cesium Double Cation Lead Halide Perovskite Nanowires and Nanosheets with Improved Stability

Abstract: Lead halide perovskites with well-defined morphology have attracted attention for their unique properties as a promising new class of semiconductor materials in photovoltaics and optoelectronics. However, controlling morphologies and compositions of perovskite nanostructures with improved stability, especially for double cation lead halide perovskite, still remains a challenge. Here, we demonstrate a colloidal synthetic approach for direct synthesis of stable singlecrystal formamidinium (FA) cesium double cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 52 publications
4
70
0
Order By: Relevance
“…g) Schematic illustration for the formation of perovskite nanowires and nanosheets NCs. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…g) Schematic illustration for the formation of perovskite nanowires and nanosheets NCs. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…Moreover, by using large amount of OLA, the PNC surface became more protected in all directions and formed nanocubes, while otherwise nanorods were formed (Figure f) . Wang's group found that by tuning the ligand participating in the reaction such as changing the amount of OAC and oleylamine, different shapes of PNCs can be achieved, such as nanowires or nanosheets (Figure g) . Since halide atoms can easily escape from the PNCs, resulting in their poor stability, surface passivation can be used to form more stable halide–hydrogen bonds on the surface, which could inhibit the capture of the excited electrons .…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…Fortunately, we can reduce breakage of nanowires by optimizing the parameters, such as growth time and the concentration of the solution during anion exchange. Compared with the previous reports, a large number of nanowires being fractured [32,33], and bottom of nanowires films becoming turbid owing to high temperatures [35], our method can protect the morphology of nanowires successfully and provide convenience for fabricating nanowire-based devices.…”
Section: Resultsmentioning
confidence: 87%
“…In the family of halide perovskites, CsPbBr 3 is particularly attractive in the field of photodetectors and light-emitting diodes due to its suitable band gap and high quantum efficiency [14,29]. Thus, nanowires based on CsPbBr 3 have been reported widely [28,[30][31][32][33]. In these reports, most of the nanowires were prepared by the traditional hot-injection technique [32], but when these nanowires are used for films, complex vacuum coating technology will be necessary [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation